One-step immobilization-purification of enzymes by carbohydrate-binding module family 56 tag fusion. (30th November 2019) - Qin, Zhen; Lin, Si; Qiu, Yongjun; Chen, Qiming; Zhang, Yin; Zhou, Jiachun; Zhao, Liming
Highlights: Our study provides a nontoxic and inexpensive enzyme immobilization strategy. CBM56-Tag enable the one-step immobilization-purification of enzyme with curdlan. CBM56-Tag bind to curdlan by hydrogen-bond and hydrophobic interaction. The immobilized enzyme could be directly used in the packed-bed reactor. Abstract: Immobilization of enzymes is an essential strategy with outstanding prospects in biocatalytic processes. Nontoxic, inexpensive immobilized enzyme approach is especially important for food enzymes. We here demonstrate that a carbohydrate-binding module family 56 domain (CBM56-Tag) mediates the immobilization of fusion enzymes with the curdlan (β-1, 3-glucan) particle support, thereby enabling the one-step immobilization-purification of target enzymes. CBM56-Tag exhibits an immunoglobulin-like β-sandwich fold, which can be adsorbed by curdlan via hydrogen bond-mediated binding. The maximum adsorption capacity of a fusion chitosanase (CBM56-GsCsn46A) on curdlan is 50.72 mg/g. The immobilized enzyme could be directly used in the packed-bed reactor. This immobilization strategy utilizes a natural polysaccharide without any treatment, avoiding the negative environmental effects. Moreover, the one step immobilization-purification simplifies the purification step, which reduces the use of chemicals. Our study provides a nontoxic and inexpensive immobilization strategy for the biocatalytic reaction in food industry.